Dynamic deuterium retention properties of tungsten measured using laser-induced breakdown spectroscopy. (4th October 2021) - Nishijima, D.; Doerner, R.P.; Baldwin, M.J.; Tynan, G.R.
Abstract: Dynamic deuterium (D) retention properties of tungsten (W) are investigated under steady-state D plasma exposure in the PISCES-A linear plasma device. In contrast to static retention, dynamic retention is quickly released from the material at the termination of the incident plasma flux, and thus in-operando laser-induced breakdown spectroscopy (LIBS) measurements have been conducted during steady-state D plasma exposure. A procedure is, first, established to extract the dynamic retention component from the in-operando LIBS D I 656.1 nm line intensity, which can contain contributions from dynamic and static retention as well as background D/D2 gas, excited by both steady-state and laser-induced plasmas. Using the developed procedure, the dynamic D retention in W is systematically examined while scanning the following plasma exposure parameters: incident ion energy, E i, sample temperature, T s, incident ion flux, Γi . No clear E i dependence is seen in the range of E i ∼ 45–175 eV, as expected from a small variation in the average implantation depth (∼3–6 nm) of D in W. The dynamic retention is found to monotonously decrease with increasing T s from 348 to 573 K, while the total static retention is reported to peak at T s ∼ 500–600 K. It is revealed that the dynamic retention linearly increases with increasing Γi, and then saturates at Γi ⩾ 0.75 × 10 21 m −2 s −1 . Possible physical mechanisms for the observed dependence of the dynamic retention on T s and Γi are discussed. Furthermore, sequential pure He, followed by pure D, plasma exposures show that the dynamic D retention is not strongly affected by He bubbles in the near-surface region.